Rediscovering the New World : inter-American literature in a comparative context - Fitz, Earl E. (University of Iowa Press, 1991)
The concept of "American" literature is not the exclusive province of any one nation. Thanks to the historical circumstances that governed the European conquest and settlement of the Americas, we can and should approach the writings of English and French Canada, the United States, Spanish America, and Brazil as a cohesive group of American literature, worthy of study without constant reference to European texts. Now, Rediscovering the New World makes a timely addition to this expanding field on Inter-American scholarship that should help lead tothe formation of a new canon. Th